(untitled) (The Pakistan Development Review, 2020)
Taxes are involuntary charges levied on individuals or corporations and enforced by a government entity—whether local, subnational or national—in order to finance government activities. As such, the prime objective of the taxes is revenue generation. However, for sustained stream of revenues, the tax policy also needs to be growth facilitating. These dual objectives can only be achieved if the tax policy reduces the deadweight loss resulting from imposition of taxes, and help transactions grow. Higher number of transactions is associated with higher economic growth and more employment. Increased growth enhances the taxable capacity of the economy and therefore generate sustainable streams of revenues.